Speed Model Processing using Ray Tracing Method for 2D Depth Domain Migration (Pre Stack Depth Migration) on the field "AV" - Evita, Anjar; Danusaputro, Hernowo (JURNAL SAINS DAN MATEMATIKA, 2014)
The research was conducted to process 2D seismic data by Pre Stack Depth Migration (PSDM) method on the field â€œAVâ€. The purpose of this study was to determine the appropriate interval velocity model to manage the PSDM methods work. Interval velocity model obtained from the initial estimate using coherency inversion velocity model is usually not convergent. Interval velocity model should be improved through several stages in order the estimated speed could be closer to the actual speed value. Some initial interval velocity model parameters should be improved to be more sensitive to lateral velocity variations for PSDM work. The method used to improve the velocity model was a horizon-based tomography using the ray tracing concept. These methods improved the layer speed and reflector geometry to produce a new interval velocity model. Model errors should be corrected by residual move out analysis. The best analysis obtained was from the fifth iteration to eliminate errors and flatten depth gathers. The proper value of the speed produced good quality images. The results of this research was PSDM Section or PSDM cross-section. PSDM cross-section has a good image quality to represent the geological structures in the earth's sub surface.